MiR‐193a/b‐3p relieves hepatic fibrosis and restrains proliferation and activation of hepatic stellate cells. Issue 6 (3rd April 2019) - Ju, Baoling; Nie, Ying; Yang, Xufang; Wang, Xiaohua; Li, Fujuan; Wang, Meng; Wang, Chuang; Zhang, Hongjun
Abstract: MicroRNAs (miRNAs) have been confirmed to participate in liver fibrosis progression and activation of hepatic stellate cells (HSCs). In this study, the role of miR‐193a/b‐3p in concanavalin A (ConA)‐induced liver fibrosis in mice was evaluated. According to the results, the expression of miR‐193a/b‐3p was down‐regulated in liver tissues after exposure to ConA. Lentivirus‐mediated overexpression of miR‐193a/b‐3p reduced ConA‐induced liver injury as demonstrated by decreasing ALT and AST levels. Moreover, ConA‐induced liver fibrosis was restrained by the up‐regulation of miR‐193a/b‐3 through inhibiting collagen deposition, decreasing desmin and proliferating cell nuclear antigen (PCNA) expression and lessening the content of hydroxyproline, transforming growth factor‐β1 (TGF‐β1) and activin A in liver tissues. Furthermore, miR‐193a/b‐3p mimics suppressed the proliferation of human HSCs LX‐2 via inducing the apoptosis of LX‐2 cells and lowering the levels of cell cycle‐related proteins Cyclin D1, Cyclin E1, p‐Rb and CAPRIN1. Finally, TGF‐β1 and activin A‐mediated activation of LX‐2 cells was reversed by miR‐193a/b‐3p mimics via repressing COL1A1 and α‐SMA expression, and restraining the activation of TGF‐β/Smad2/3 signalling pathway. CAPRIN1 and TGF‐β2 were demonstrated to be the direct target genes of miR‐193a/b‐3p. We conclude that miR‐193a/b‐3p overexpression attenuates liver fibrosis through suppressing the proliferation and activation of HSCs. Our data suggest that miR‐193a‐3p and miR‐193b‐3p may be new therapeutic targets for liver fibrosis.